Perceived value, relationship quality and customer engagement in restaurant service context - Nguyễn Hữu Khôi (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2021)
This study discusses and tests the relationships between perceived value, relationship quality, and customer engagement in the Vietnamese restaurant service context. Accordingly, perceived value is hypothesized to have a direct and indirect effect on customer engagement via relationship quality. The hypothesis testing results on a sample of 219 customers in Ho Chi Minh City indicate that perceived value directly affects relationship quality and customer engagement while also has an indirect effect on customer engagement via relationship quality. Based on the findings, we propose some theoretical and practical implications for restaurant management activities.